Difficulties in sensory integration, affectivity, and behavior among students from a public school - Erazo, Oscar Armando (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Sensory integration is a neuropsychological process which allows an appropriate processing of information, with implications for cognitive functionality, learning, affectivity, and behavior. Its deficiency affects 35% of students in South America and its complex presentation confuses professionals who seek to classify it. For this reason, a study with a quantitative approach is constructed; it describes the variables of sensory integration, learning, affectivity, and behavior in a non-probabilistic sample of 66 students between 7 and 10 years old from a public school. The results confirm the existence of a sensory integration problem in 46% of people, difficulties in learning to read of 58% and in learning calculus of 93%, anxiety of 20 and 35%, depression between 15 and 31%, and behavioral problems of 15%, for which identification and intervention programs in schools are required.